The Strength of Sound Corporate Governance on Economic Growth in an Emerging Market Context - Maune, Alexander (International Journal of Economics and Financial Issues, 2017)
The study examined the impact of sound corporate governance on economic growth in an emerging market, Zimbabwe, using an econometric model. A multiple linear regression analysis was employed to examine the relationship. Secondary data for the period from 1968 to 2015 was collected from World Bank`s Worldwide Governance and World Development Indicators databases. It was found that sound corporate governance is significantly related to economic growth in an emerging market, Zimbabwe, in a positive and negative manner with a p-value of 0.000023235 at 5% level of confidence. On one hand, control of corruption is negatively significantly related to economic growth and on the other hand political stability and absence of violence/terrorism positively significantly related to economic growth. Government effectiveness, regulatory quality, rule of law and voice and accountability are insignificant in influencing economic growth in Zimbabwe at 5% level of significance. The findings from this article will assist policy formulation, policy implementation and future research. This article, however, is of great importance to government, private sector and the academia. Keywords: Corporate Governance; Economic Growth; Economic Development; Gross Domestic Product; Investor Protection; Emerging Market. JEL Classifications: O11, O16, F43, G34, M14